2004
DOI: 10.1007/s00423-003-0427-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of perforated gastroduodenal ulcer by running suture

Abstract: The closure of perforated gastric ulcers with the Lahodny suture is safe and simple to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There are other treatment options for perforated peptic ulcer such as Billroth I, Billroth II, and truncal vagotomy drainage procedure [11,12]. Laparoscopic repair of perforated gastroduodenal ulcer by running suture is an option [13]. Gastric ulcer rarely presents with perforation peritonitis; gastric perforations are related to the widespread use of NSAIDs [14].…”
Section: Discussionmentioning
confidence: 99%
“…There are other treatment options for perforated peptic ulcer such as Billroth I, Billroth II, and truncal vagotomy drainage procedure [11,12]. Laparoscopic repair of perforated gastroduodenal ulcer by running suture is an option [13]. Gastric ulcer rarely presents with perforation peritonitis; gastric perforations are related to the widespread use of NSAIDs [14].…”
Section: Discussionmentioning
confidence: 99%
“…There remains no consensus in the literature as to the ideal method of PPU repair although multiple techniques have been described. 18,21,22,[38][39][40] In our study, the method of repair was left to the discretion of the operating surgeon ( Table 2). There were no incidences of post-operative leak or morbidity due to the technical factors in ulcer repair.…”
Section: Discussionmentioning
confidence: 99%
“…We have not seen any leak or fistula formation with this suture. Koninger et al [12] has reported the safe use of PDS Lahodny suture. In his opinion, the advantages of this monofilament running suture may lie in meticulous closure of the perforation and easier closure of the defect with rigid edges.…”
Section: Discussionmentioning
confidence: 99%